Immunotherapy utilization in stage IIIA melanoma: less may be more - Frey, Alexander E.; Kerekes, Daniel M.; Khan, Sajid A.; Tran, Thuy T.; Kluger, Harriet M.; Clune, James E.; Ariyan, Stephan; Sznol, Mario; Ishizuka, Jeffrey J.; Olino, Kelly L. (Frontiers in Oncology, 2024)
Background: Immunotherapy agents are approved for adjuvant treatment of stage III melanoma; however, evidence for survival benefit in early stage III disease is lacking. Current guidelines for adjuvant immunotherapy utilization in stage IIIA rely on clinician judgment, creating an opportunity for significant variation in prescribing patterns. This study aimed to characterize current immunotherapy practice variations and to compare patient outcomes for different prescribing practices in stage IIIA melanoma. Study Design: Patients with melanoma diagnosed from 2015-2019 that met American Joint Committee on Cancer 8th edition criteria for stage IIIA and underwent resection were identified in the National Cancer Database. Multiple imputation by chained equations replaced missing values. Factors associated with receipt of adjuvant immunotherapy were identified. Multivariable Cox proportional hazards regression compared overall survival across groups. Results: Of 4,432 patients included in the study, 34% received adjuvant immunotherapy. Patients had lower risk-adjusted odds of receiving immunotherapy if they were treated at an academic center (OR=0.48, 95%CI=0.33-0.72, p<0.001 vs. community facility) or at a high-volume center (OR=0.69, 0.56-0.84, p<0.001 vs. low-volume). Immunotherapy receipt was not associated with risk-adjusted survival (p=0.095). Moreover, patients treated at high-volume centers experienced longer overall risk-adjusted survival than those treated at low-volume centers (HR=0.52, 0.29-0.93, p=0.030). Risk-adjusted survival trended toward being longer at academic centers than at community centers, but the difference was not statistically significant. Conclusion: Academic and high-volume centers utilize significantly less adjuvant immunotherapy in stage IIIA melanoma than community and low-volume centers without compromise in overall survival. These findings suggest that this population may benefit from more judicious immunotherapy utilization.